(untitled) (The International Journal for Scientific Research, 2023)
The central bank is a supreme authority to which all financial institutions are subject, and it is also concerned with managing the economy to maintain its stability from financial fluctuations and the disadvantages of high prices, so the central bank implements its policies and instructions through these institutions that make up the economy, so any measure or action it takes is affected by these institutions and then the economy. The interest is one of the tools that the Central Bank uses in all its actions and procedures to manage institutions. Institutions that deal with interest respond and interact with its procedures and instructions. As for those that do not deal with interest, such as Islamic financial institutions, they do not respond to what the central bank issues, as it differs from the nature and mechanism of its banking work and the privacy of many Its actions resulting from the source of its legislation, and therefore the Central Bank faces the possibility of violating the legal prohibitions controlling it, which makes it difficult to monitor the task.